2019
DOI: 10.3390/catal9100785
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Electronic Changes of the CeO2 Support during CO Oxidation on Au/CeO2 Catalysts: Time-Resolved Operando XAS at the Ce LIII Edge

Abstract: While being highly active for the CO oxidation reaction already at low temperatures, Au/CeO2 catalysts suffer from continuous deactivation with time on stream, with the activity and deactivation depending on the initial catalyst activation procedure. In previous X-ray absorption measurements at the Au LIII edge, which focused on changes in the electronic and geometric changes of Au, we found a modest increase of the Au particle size during reaction, with the Au nanoparticles (NPs) present in a dominantly metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…In the next step, the as prepared Au/CeO 2 catalyst precipitate was washed with deionized water and subsequently dried at room temperature overnight (≥12 h). Different loadings of Au in the range between 2 and 5 wt.% were used [28,36,38,46,47,54] . It should be mentioned that the proper selection of the surface morphology of CeO 2 is also an additional parameter that can be controlled in the catalyst synthesis to steer the catalytic properties of resulting Au/CeO 2 catalysts.…”
Section: Recipe For the Preparation Of Au/ceo2mentioning
confidence: 99%
See 1 more Smart Citation
“…In the next step, the as prepared Au/CeO 2 catalyst precipitate was washed with deionized water and subsequently dried at room temperature overnight (≥12 h). Different loadings of Au in the range between 2 and 5 wt.% were used [28,36,38,46,47,54] . It should be mentioned that the proper selection of the surface morphology of CeO 2 is also an additional parameter that can be controlled in the catalyst synthesis to steer the catalytic properties of resulting Au/CeO 2 catalysts.…”
Section: Recipe For the Preparation Of Au/ceo2mentioning
confidence: 99%
“…Focusing first on the pretreatment effect we can also see a pronounced effect of the treatment gas on the resulting chemical properties of CeO 2 . While the oxidative pretreatment (O400) resulted in about perfect CeO 2 structure (Ce exists mainly as Ce 4+ ), with a negligible Ce 3+ ions concentration, XANES spectra at the Ce L III edge showed a notable reduction of CeO 2 both after the reductive CO400 and the H400 pretreatments [54] …”
Section: Electronic and Chemical Properties Of Au/ceo2 Catalystsmentioning
confidence: 99%
“…It was found that the reduction state of the ceria support strongly affects the catalytic activity. Moreover, oxygen mobility and charge transfer processes induce the reduction at both surface and subsurface of the catalyst …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the reducibility of the support is also an important criterion for evaluating catalyst performance. [ 48 ] Both phenomena are affected by the type, size, and distribution of oxygen vacancies on the CeO 2 surface, [ 49 ] so‐called oxygen vacancies, including single, double, and multiple oxygen vacancies, as well as surface, subsurface, and bulk vacancies. The amount of oxygen vacancies depends on the reduction degree of the catalyst, which is related not only to the environment, but also to the nanostructure of the catalyst.…”
Section: Loading Metals Onto Ceo2mentioning
confidence: 99%